Historical Shark Meat Consumption and Trade Trends in a Global Richness Hotspot - Márcio L. V. Barbosa-Filho; Rachel Ann Hauser-Davis; Salvatore Siciliano; Thelma L. P. Dias; Rômulo R. N. Alves; Eraldo M. Costa-Neto (Ethnobiology Letters, 2019)
Shark catches have increased worldwide, threatening the survival of several species. This study describes historical trends concerning shark consumption and commercialization by artisanal fishers in northeastern Brazil. Semi-structured questionnaires were applied and respondents pointed out that sharks used to be locally regarded as low-quality fish in the past and rejected by fish consumers, with low fisher consumption frequency. However, this has changed in recent decades, as a total of 95.4% (n=62) of the questionnaire respondents reported currently consuming shark meat, while 61.5% (n=40) highlighted its high quality. In addition, most interviewees (90.8%; n=59) reported decreasing numbers of sharks caught over time, following worldwide trends, leading to decreased fisher access to shark meat. Because of this, most respondents (70.7%, n=46) now consider it more advantageous to sell the sharks they catch than to consume them. In addition, the local commercialization of these fish is currently based on immature coastal species (<1 m). Thus, economic and biological studies on local shark populations are suggested in order to preserve local fisher culture and ensure food security for artisanal fisher communities and a long-term sustainable fishery and conservation of exploited species.